Towards innovative environmental management in the Agro-food Industry - Bremmers, Harry; Haverkamp, Derk-Jan; Sabidussi , Anna; Omta, Onno (Applied Studies in Agribusiness and Commerce, 2008)
This article focuses on the problem: what external (stakeholder) and (internal structural/organizational) factors drive companies in the food- and agribusiness towards innovative environmental management? Innovative companies are those considered to have adopted a supply chain perspective, instead of a focus on the single business unit. We propose that innovativeness is associated with stakeholder wishes (the government, the public environmental policy being a major influential factor), in combination with structural characteristics of the firm (like R&D-efforts, culture and managerial competences). We surveyed 492 companies in 2002, to get insight into the causes of innovativeness in the Dutch agri-food sector, and supplemented this data by means of a similar questionnaire in 2005. Structural equation modeling and correlation analysis were applied. The research provided evidence that companies are restricted by, and therefore not comfortable with, public environmental policies, which seem to obstruct innovativeness rather than stimulate it. Firms that(1) have enough internal (physical, financial, social)resourcestoinnovate, and (2) are more embedded in a web of (commercial) stakeholder wishes, prove to be more innovative. Suggestions are made to shift the corporate and public policies towards a supply chain-oriented approach by granting benefits for vertical cooperation in supply-chains.